A STUDY OF BILINGUAL EFFECTS IN ENHANCING COGNITIVE ABILITY OF EFL STUDENTS IN E-LEARNING CLASS - Andi Ilmi (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
This study aims to determine how the use of favorable bilingual activities effect in enhancing the cognitive abilities of EFL students in the E-Learning class. Researcher used E-Learning class observation through the google meet application as well as student and lecturer interviews as a qualitative research instrument. The results of this study indicate that the habit of using bilingual activities is one way to improve students' cognitive in terms of mastery of 2 languages ​​in participating in E-Learning classes. It turns out that the role of the lecturer is one of the determining factors for the success of this bilingual activity, while the factor of the lack of data and network quotas makes students not focus on learning so that it hinders students' cognitive abilities. The results obtained prove that the way bilingual activity effect the enhancement of students' cognitive abilities in the E-Learning class is to make it a habit which mostly influenced by lecturer actions. keywords: Bilingual, Bilingual Activity, Cognitive Ability